2016
DOI: 10.4238/gmr.15016084
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of food-borne Staphylococcus aureus enterotoxin genes

Abstract: ABSTRACT. We identified and analyzed 5 new-type enterotoxin genes, including SEj, SEl, SEq, SEm, and SEr, to explore the distribution of 5 enterotoxin genes in Staphylococcus aureus of different origins as well as their correlations and differences. We examined the distribution of the S. aureus enterotoxin genes and their pathogenic mechanisms. A total of 660 specimens were collected from January 2011 to December 2014, and 217 strains of S. aureus were isolated. The template DNA of S. aureus was extracted. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Another bacterium, S. aureus, which belongs to the Gram-positive Micrococcaceae family, is considered to be one of the most common causes of foodborne disease in the world [10]. This bacterium causes gastrointestinal illness by secreting a range of toxins, including staphylococcal enterotoxins [10][11][12]. S. aureus is also able to form biofilms on food-contact surfaces, which highly increases its stress tolerance and, thus, its persistence in food-related environments [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Another bacterium, S. aureus, which belongs to the Gram-positive Micrococcaceae family, is considered to be one of the most common causes of foodborne disease in the world [10]. This bacterium causes gastrointestinal illness by secreting a range of toxins, including staphylococcal enterotoxins [10][11][12]. S. aureus is also able to form biofilms on food-contact surfaces, which highly increases its stress tolerance and, thus, its persistence in food-related environments [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al showed five new types of enterotoxin genes, namely SEj, SEl, SEq, SEm, and SEr. Of these, SEj and SEr were detected in 16.6% and 14.3%, respectively [ 65 ]. Additionally, SEi (97.2%) and SEm (86.1%) were frequently detected in retail foods in China [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the five new enterotoxin genes were extensively present in proteins of animal origin compared with that from other origins. This is related to the animal characteristics and interaction with the living environment, operation environment for food processing, and storage environment for finished products [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data were processed using the 2 −ΔΔ C t method, and GhActin and NS Stage 1 were used as internal controls. All of the primer pairs ( Table S9 ) used for qPCR were designed using Oligo 7 [ 67 ].…”
Section: Methodsmentioning
confidence: 99%